An Overview Of Inbound Marketing At Wan International Technology Companies - Husaeni, Fadly; Nurendah, Yulia; Zuhdi, Saefudin (Jurnal Aplikasi Bisnis Kesatuan, 2023)
Indonesia potential and challenges for the information technology and telecommunications industry.This is due to its large population and strategic geographical location. To achieve optimal results inmarketing activities with the help of technology, one of the strategies is inbound marketing. Inbound marketing is a series of activities implemented by companies to attract potential buyers through engagingcontent and satisfying their needs. The objectives of this Final Project are: 1) To determine how the implementation of inbound marketing at WAN International Technology Companies; 2) To identify thebarriers to implementing inbound marketing at An Overview of Inbound Marketing at WAN International Technology Companies; 3) To explore efforts to overcome the barriers to implementing inbound marketingat WAN International Technology Companies. The findings of this Final Project are: 1) The implementationof inbound marketing includes email marketing, blog posts, SEO (Search Engine Optimization), display advertising, and social networks. 2) The challenges in implementing inbound marketing include errors in email subject lines, selecting blog topics, internal factors within the company, targeting unpopular keywords, slow indexing of the website by Google due to competitors implementing similar SEO strategies, and ineffective business promotional content and hashtag optimization. 3) Efforts to overcome these challenges include Blast Email, Educational Articles, Search Engine Marketing (SEM), VideoAdvertising, and Research Content Marketing.